2018
DOI: 10.2478/aoas-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

The uses of microbial phytase as a feed additive in poultry nutrition – a review

Abstract: most of the phosphorus (p) in feed ingredients is present as phytate, which is poorly available for absorption in the gastrointestinal tract of different poultry species due to the lack of endogenous phytase. The supplementation of phytase increases the utilization of p by hydrolyzing phytate, which consequently may reduce the excretion of p in the environment. in addition, it has been suggested that phytase may improve the feed utilization, weight gain, egg production and egg traits, nutrient digestibility, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 79 publications
1
60
0
2
Order By: Relevance
“…For many years there have been attractive alternative approaches and technologies to address these problems. For the P management issue, there is the use of phytase (phytic acid-specific phosphohydrolases; myo-inositol hexakisphosphate 3-and 6-phosphohydrolase; EC 3.1.3.8 and EC 3.1.3.26) as a feed additive [7,8] and for the human mineral nutrition problem, there is "biofortification" breeding for enhanced mineral density [9]. Both of these alternatives are less challenging to implement and more readily accessible than breeding the lpa trait and perhaps in specific cases have advantages over it, resulting in much wider acceptance, utilization and recognition.…”
Section: Introduction: the Low Phytic Acid Traitmentioning
confidence: 99%
“…For many years there have been attractive alternative approaches and technologies to address these problems. For the P management issue, there is the use of phytase (phytic acid-specific phosphohydrolases; myo-inositol hexakisphosphate 3-and 6-phosphohydrolase; EC 3.1.3.8 and EC 3.1.3.26) as a feed additive [7,8] and for the human mineral nutrition problem, there is "biofortification" breeding for enhanced mineral density [9]. Both of these alternatives are less challenging to implement and more readily accessible than breeding the lpa trait and perhaps in specific cases have advantages over it, resulting in much wider acceptance, utilization and recognition.…”
Section: Introduction: the Low Phytic Acid Traitmentioning
confidence: 99%
“…With the rise of population in the world and decrease in the use of lands for agriculture practices, several approaches in agriculture systems involve the culture of plants in salinity land for animal feeding [1,2]. Moreover, many countries are suffering from scarcity of freshwater with an increase in the ambient temperature which had led to a decrease in the availability of freshwater.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous enzyme supplementation is also widely used to enhance the degradation of soybean protein and inactive anti-nutritional factors during the SSF of SBM (Ma and Wang 2010;Amadou et al 2011). Dietary enzyme supplementation improves the nutritional status and growth performance of broilers (Abudabos 2012;Abudabos and Yehia 2013;Abd El-Hack et al 2018). However, to our knowledge, no study has reported the fermentation conditions of exogenous proteases and probiotics for the SSF of SBM.…”
Section: Introductionmentioning
confidence: 99%